Representasi Homoseksualitas di Kalangan Remaja Awal dalam Film ‘Monster’ - N, Nabila Dwita (Program Studi Ilmu Komunikasi Universitas Negeri Padang, 2024)
Sexuality remains a taboo topic, particularly regarding early adolescents. The film Monster presents an engaging narrative that explores the experiences of LGBTQ adolescents as they navigate their sexuality. This study employs Semiotic Analysis based on C.S. Peirce’s triangle of meaning to examine the signs and meanings that represent homosexuality during early adolescence. Additionally, it analyzes the forms of acceptance and rejection of homosexuality as depicted by the characters and observed by others in Monster. The findings indicate that the experiences of LGBTQ adolescents are predominantly tragic due to an unsupportive environment. The film illustrates subtle gestures through which adolescents express their LGBTQ identity, such as coming out and the concept of the closet.